2010
DOI: 10.1152/jn.00019.2010
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Balance and Mechanotransduction in Rat Cochlear Hair Cells

Abstract: Auditory transduction occurs by opening of Ca(2+)-permeable mechanotransducer (MT) channels in hair cell stereociliary bundles. Ca(2+) clearance from bundles was followed in rat outer hair cells (OHCs) using fast imaging of fluorescent indicators. Bundle deflection caused a rapid rise in Ca(2+) that decayed after the stimulus, with a time constant of about 50 ms. The time constant was increased by blocking Ca(2+) uptake into the subcuticular plate mitochondria or by inhibiting the hair bundle plasma membrane C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
119
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(130 citation statements)
references
References 80 publications
9
119
1
Order By: Relevance
“…This finding is consistent with Ca 2+ entry driving adaptation as demonstrated in hair cells from lower vertebrates (9,10). Additional evidence for the presence of MET current adaptation is the channels' increased resting open probability when Ca 2+ influx into the stereocilia is decreased (9,12,28,29), which was evident in OHCs at +99 mV ( Fig. 1 A and E; see also Fig.…”
Section: Significancesupporting
confidence: 86%
See 2 more Smart Citations
“…This finding is consistent with Ca 2+ entry driving adaptation as demonstrated in hair cells from lower vertebrates (9,10). Additional evidence for the presence of MET current adaptation is the channels' increased resting open probability when Ca 2+ influx into the stereocilia is decreased (9,12,28,29), which was evident in OHCs at +99 mV ( Fig. 1 A and E; see also Fig.…”
Section: Significancesupporting
confidence: 86%
“…To probe the direct dependence of MET current adaptation on intracellular Ca 2+ , recordings from mouse cochlear hair cells were performed by using either low, endolymphatic extracellular Ca 2+ (0.04 mM: see Materials and Methods) or different intracellular concentrations of the fast Ca 2+ chelator 1,2-Bis (2-aminophenoxy)ethane-N,N,N′,N′-tetraacetic acid (BAPTA). Extracellular Ca 2+ is known to block the current through the MET channels with a half-blocking concentration of 1 mM (12,29). We found that reducing extracellular Ca 2+ from 1.3 mM ( Fig.…”
Section: Modulation Of Met Current Adaptation By Extracellular and Inmentioning
confidence: 67%
See 1 more Smart Citation
“…Such subcuticular aggregation of mitochondria with large volumes and surface areas, and "tethering" (34,35) indicate the need for tight control of calcium homeostasis or that the SO, SRs, and other structures in the apical part of the hair cell may have high energetic requirements. Recent experiments in cochlear outer hair cells demonstrated that apical mitochondria can act to block Ca 2+ diffusion into the hair-cell soma (36). In addition, mitochondrial crista structure has recently been related to the high metabolic rate of synapses at the calyx of Held (33).…”
Section: Discussionmentioning
confidence: 99%
“…K + depolarization induces not only reversible shape changes in type I hair cells (39)(40)(41), but also a rise in cytosolic Ca 2+ concentration (42) that could trigger such changes. Rising Ca 2+ levels have been suggested as a potential substrate for mechanotransduction (3), with the large SO-associated mitochondria potentially playing a role (36,43) by promoting reuptake of Ca 2+ after mechanotransduction. A prior study (44) has shown that in the presence of local elevated calcium levels, fodrin (α-2 spectrin) can change from a diffuse distribution within the cytoplasm to a submembranous position, or a patch.…”
Section: Discussionmentioning
confidence: 99%